2013
DOI: 10.1016/j.tiv.2012.12.018
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity and genotoxicity studies of titanium dioxide (TiO2) nanoparticles in Chinese hamster lung fibroblast cells

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 65 publications
2
63
0
2
Order By: Relevance
“…29,30 Some studies have demonstrated in vitro cytotoxicity and genotoxicity of TiO 2 NPs in various cell lines, plants, and brains of mice after oral administration. 3133 Bioaccumulation, subacute toxicity, and tissue distribution of TiO 2 NPs was exhibited in goldfish ( Carassius auratus ) and C57BL/6 mice. 34,35 …”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 99%
“…29,30 Some studies have demonstrated in vitro cytotoxicity and genotoxicity of TiO 2 NPs in various cell lines, plants, and brains of mice after oral administration. 3133 Bioaccumulation, subacute toxicity, and tissue distribution of TiO 2 NPs was exhibited in goldfish ( Carassius auratus ) and C57BL/6 mice. 34,35 …”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 99%
“…Substancja ta wywołuje uszkodzenia DNA w ludzkich komórkach i komór-kach ssaków, szczególnie w przypadku ekspozycji na nanocząstki TiO 2 (20-30 nm) (35,36). Efekt ten wzmacnia wcześniejsze napromieniowanie komórek Prace, w których badano różne wielkości czą-stek ditlenku tytanu, wykazały, że cząstki mniejsze niż 100 nm wywołują większe zmiany, co jest skorelowane z większą powierzchnią cząstek (22)(23)(24).…”
Section: Działanie Mutagenne I Genotoksyczneunclassified
“…52 In agreement with this understanding, TiO 2 -mediated ROS production has indeed been shown to have DNA damaging and mutagenic potential, [53][54][55][56] and a variety of other genotoxic in°uences. [57][58][59][60][61][62] Similarly, chromosomal breakages or disruptions can result from UV-mediated exposure to ZnO nanoparticles. 63 Using human dermal¯broblasts, we also showed that exposure to ZnO resulted in DNA fragmentation which activated tumor suppressor gene p53 and subsequent cell death.…”
Section: Toxicological In°uencesmentioning
confidence: 99%